Analisis Dampak Implementasi IFRS 9 Terhadap Penilaian Aset dan Kewajiban Keuangan: Tinjauan dari Perspektif Perusahaan Publik - Klemens Mere; I Ketut Kusuma Wijaya; Pandu Adi Cakranegara; Agung Nurmansyah; Delfian Zaman (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This article aims to analyze the impact of the implementation of International Financial Reporting Standards (IFRS) 9 on the valuation of financial assets and liabilities from the perspective of public companies. The literature review method is employed to gather and analyze various studies and literature related to the implementation of IFRS 9. From the literature review findings, it is revealed that the implementation of IFRS 9 has significant impacts on the valuation of financial assets and liabilities of public companies. Changes in the classification, recognition, and measurement of financial instruments can affect the financial statements and performance of companies. The importance of a deep understanding of this standard increases with the growing complexity of financial instruments. Three relevant keywords in this article are IFRS 9, financial asset valuation, and public companies. This article is expected to provide additional insights to practitioners, regulators, and academics regarding the implications of implementing IFRS 9 in the context of valuing financial assets and liabilities of public companies. Keywords: IFRS 9, financial asset valuation, public companies.